Human peripheral blood mononuclear cells enriched in endothelial progenitor cells via quality and quantity controlled culture accelerate vascularization and wound healing in a porcine wound model. Issue 7 (July 2018) - Kado, Makiko; Tanaka, Rica; Arita, Kayo; Okada, Kayoko; Ito-Hirano, Rie; Fujimura, Satoshi; Mizuno, Hiroshi
The transplantation of endothelial progenitor cells (EPCs) is used to promote wound angiogenesis. In patients with chronic wounds and accompanying morbidities, EPCs are often compromised in number and function. To overcome these limitations, we previously developed a quality and quantity controlled (QQ) culture system to enrich peripheral blood mononuclear cells (PBMNCs) in EPCs. To evaluate the wound healing efficacy of mononuclear cells (MNCs) harvested after QQ culture (QQMNCs), preclinical studies were performed on large animals. MNCs harvested from the blood of healthy human subjects were cultured in the presence of angiogenic cytokines and growth factors in a serum-free medium for 7 days. A total of 5 × 10 6 QQMNCs per full-thickness skin defect or control saline was injected into wounds induced in cyclosporine-immunosuppressed pigs. EPC colony-forming assays revealed a significantly higher number of definitive (partially differentiated) EPC colony-forming units in QQMNCs. Flow cytometry evaluation of QQMNC surface markers showed enrichment of CD34 + and CD133 + stem cell populations, significant reduction in CCR2 + cell percentages, and a greater than 10-fold increase in the percentage of anti-inflammatory M2-type macrophages (CD206 + cells) compared with PBMNCs. Wounds treated with QQMNCs had a significantly higher closure rate. Wounds were harvested, frozen, and sectioned at day 21 postoperatively. Hematoxylin and eosin staining revealed that the epithelization of QQMNC-treated wounds was more advanced than in controls. Treated wounds developed granulation tissue with more mature collagen and larger capillary networks. CD31 and human mitochondrial co-staining confirmed the presence of differentiated human cells within newly formed vessels. Real-time polymerase chain reaction (PCR) showed upregulation of interleukin 6 (IL-6), IL-10, and IL-4 in the wound bed, suggesting paracrine activity of the transplanted QQMNCs. Our data demonstrate for the first time that QQ culture of MNCs obtained from a small amount of peripheral blood yields vasculogenic and therapeutic cells effective in wound healing.